The Explanation of Aesthetic Constructivism in Islamic Education - Umm ul-Banin Husayn Zadeh (پژوهش در آموزش معارف و تربیت اسلامی)
The purpose of the present study is to introduce aesthetic constructivism as a new approach in the field of Islamic education studies. Using 3 methods of qualitative content analysis, analysis, and thematic interpretation, this research dealt with the explanation of aesthetic constructivism as a new approach in the field of Islamic education studies. This idea is as a result of expanding the new approach of realist constructivism in the realm of aesthetical discussions in the Qur’ān’s instructions. In this regard and according to Islamic instructions in the Qur’ān, beauties ontologically exist in the world independent from human understanding and attention. This premise also involves the existence of God as the absolute beaty. From epistemological point of view, beauty in aesthetic constructivism is an achievable issue that has definable criteria so it can be transmitted and taught. From anthropological view, the most important part of aesthetic constructivism is the agency of a human as an agent with free will and decision-making potential who is able to create his own mental constructions from absolute beauty to achieve and resemble that according to his existence, understanding, emotion, language and special context of living; and gradually approach the ultimate human goal that is resemblance to absolute beauty.